Kedudukan Hukum Internasional Dalam Negara Dengan Sistem Hukum Nasional (The Position Of International Law In A Country With A National Legal System ) - Triadi, Irwan; Suwarsoyo, Namira Azzahra; Rahmadhany, Vania Zachra; Hantoro, Charissa Aulia; Salsabila, Marsha Isnaini; Melati, Sekar (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Globalization has cut the boundaries between national law and international law which are increasingly expanding in their role that increasingly influences the national legal systems of each country, including Indonesia as a country with a mixed legal system. This article examines the position of international law against countries with national legal systems in their integrity to maintain state sovereignty with obligations in the context of international law. In this study, the normative juridical method is used, namely the type of legal research that looks at primary and secondary legal materials such as laws, court decisions, international agreements, and doctrines and opinions of experts, where international agreements in their mechanisms must be ratified before they apply to the national legal system. Although Article 11 of the 1945 Constitution is the constitutional basis, there is no definite mechanism that regulates this integration, thus creating legal uncertainty. Strengthening regulations and harmonization are needed so that international law can be applied effectively without ignoring the sovereignty and values of Pancasila